Intravenous and tablet formulation of posaconazole in antifungal therapy and prophylaxis: A retrospective, non-interventional, multicenter analysis of hematological patients treated in tertiary-care hospitals - Heimann, Sebastian Marcel; Penack, Olaf; Egerer, Gerlinde (International journal of infectious diseases, 2019)
Objectives - Novel formulations (gastro-resistant tablet and intravenous solution) of posaconazole (POS) have been approved in prophylaxis and therapy of invasive fungal diseases (IFDs). Study aim was to analyze treatment strategies and clinical effectiveness. - Methods - We set up a web-based registry on www.ClinicalSurveys.net for documentation of comprehensive data of patients who received novel POS formulations. Data analysis was split into two groups of patients who received novel POS formulations for antifungal prophylaxis (posaconazole prophylaxis group) and antifungal therapy (posaconazole therapy group), respectively. - Results - Overall, 180 patients (151 in the posaconazole prophylaxis group and 29 in the posaconazole therapy group) from six German tertiary care centers and hospitalized between 05/2014 - 03/2016 were observed. Median age was 58 years (range: 19 - 77 years) and the most common risk factor for IFD was chemotherapy (n = 136; 76%). In the posaconazole prophylaxis group and posaconazole therapy group, median POS serum levels at steady-state were 1,068 μg/L (IQR 573-1,498 μg/L) and 904 μg/L (IQR 728-1,550 μg/L), respectively (P = 0.776). During antifungal prophylaxis with POS, nine (6%) probable/proven fungal breakthroughs were reported and overall survival rate of hospitalization was 86%. The median overall duration of POS therapy was 18 days (IQR: 7 - 23 days). Fourteen patients (48%) had progressive IFD under POS therapy, of these five patients (36%) died related to or likely related to IFD. - Conclusions - Our study demonstrates clinical effectiveness of antifungal prophylaxis with novel POS formulations. In patients treated for possible/probable/proven IFD, we observed considerable mortality in patients receiving salvage treatment and with infections due to rare fungal species.
Gesehen am 27.06.2019